2014
DOI: 10.1371/journal.pone.0098653
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Transcriptional Regulatory Network and Copy Number Variation in Intrahepatic Cholangiocarcinoma

Abstract: BackgroundTranscriptional regulatory network (TRN) is used to study conditional regulatory relationships between transcriptional factors and genes. However few studies have tried to integrate genomic variation information such as copy number variation (CNV) with TRN to find causal disturbances in a network. Intrahepatic cholangiocarcinoma (ICC) is the second most common hepatic carcinoma with high malignancy and poor prognosis. Research about ICC is relatively limited comparing to hepatocellular carcinoma, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Except for KIF7, for which no bands were detected, the remaining representatives certified the sequencing data in the investigated cell lines. While most of these proteins are components of pathways that are regulated by WWOX or AP-2α/γ (e.g., FGF [98,99], PI3K [31][32][33] and JAK/STAT [21,100] signaling), only regulation of GSK3B could be individually confirmed by literature data. Similar to observations from the current study, WWOX was found to repress GSK3B activity; such outcome results from direct binding of WWOX to GSK3B [101,102].…”
Section: Discussionmentioning
confidence: 89%
“…Except for KIF7, for which no bands were detected, the remaining representatives certified the sequencing data in the investigated cell lines. While most of these proteins are components of pathways that are regulated by WWOX or AP-2α/γ (e.g., FGF [98,99], PI3K [31][32][33] and JAK/STAT [21,100] signaling), only regulation of GSK3B could be individually confirmed by literature data. Similar to observations from the current study, WWOX was found to repress GSK3B activity; such outcome results from direct binding of WWOX to GSK3B [101,102].…”
Section: Discussionmentioning
confidence: 89%
“…Despite these challenges, investments in clinical trials geared toward molecular subpopulations of CCA patients, such as the ongoing phase 2 study of BGJ398 in CCAs with FGFR alterations (NCT02150967), for now represent the best way to improve treatment prospects for these patients. Integrative genomic analyses have characterized two intrahepatic CCA subclasses, proliferative and inflammatory, that are distinguished by unique molecular signatures and clinical features; of these, the proliferative class is associated with poorer outcomes . In the future, these subclasses may be helpful to risk stratify patients for treatment and to develop more cohesive therapeutic strategies according to the patient's profile instead of individual biomarkers.…”
Section: Next Stepsmentioning
confidence: 99%
“…Integrative genomic analyses have characterized two intrahepatic CCA subclasses, proliferative and inflammatory, that are distinguished by unique molecular signatures and clinical features; of these, the proliferative class is associated with poorer outcomes. 11,12 In the future, these subclasses may be helpful to risk stratify patients for treatment and to develop more cohesive therapeutic strategies according to the patient's profile instead of individual biomarkers.…”
Section: Next Stepsmentioning
confidence: 99%
See 2 more Smart Citations